Edukasi Bahasa Cinta Untuk Optimalisasi Pembelajaran Mental Health (SMK Syafi’i Akrom Kota Pekalongan) - Amaliyah, Amaliyah; Khotimah, Khusnul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to introduce love language education, which is to increase self-awareness, encourage social awareness, and promote mental health. Using the love language approach can have a positive impact on mental well-being, reducing levels of stress, anxiety and depression. The research method used is a qualitative method with a phenomological approach. Namely explaining or expressing the meaning of concepts or experiential phenomena based on awareness that occurs in individuals. Namely through questionnaires and observations in classes used as samples. The results of this research explain that love education methods can increase awareness about the importance of mental health, love language education can be an effective tool to support individuals in achieving optimal mental well-being. By focusing on changing speaking and thinking patterns to a more positive one, love language education can make a significant contribution to improving the quality of life of individuals and society as a whole, so that wellbeing can be realized in the student's learning process.